Development of Web-Based Learning Media on “Ability and Willingness Expression”. - Silvi Indriani; Prih Febtiningsih; Siti Niah (ELT-Lectura, 2022)
Learning is considered a standard for the success of knowledge transfer through specific processes in learning activities. Information and communication technology development has brought enormous changes to the advancement of education. Along with these developments, learning methods have undergone teaching processes. This type of research is Research and Development (R&D). The study aimed to determine the development of web-based learning media on the ability and willingness expression 8th-grade junior high school students. The results of this beta test are analyzed and used as input to improve the final product. The effectiveness test was carried out on students to determine the learning outcomes after using learning media products. The data analysis technique for web-based products' feasibility uses a Likert scale. The assessment score obtained a value in the Very Good category from the comprehensive test. This web-based learning product is effectively used as a learning media. The results of students' understanding tests on the Ability and Willingness Expression using Web-Based Learning Media can be seen from the results. Which showed an increase in learning outcomes from the pretest score to the post-test value or (N-Gain) score; of 0.71 with the category "very good”.